Kinerja Keuangan Bank Umum Syariah Di Indonesia Dengan Pendekatan Metode Market Value Added (MVA) - Yudi Siyamto; Sumadi Sumadi (ITB AAS INDONESIA Surakarta, 2018)
This study aims to determine the financial performance of the 2014-2016 Market Value Added (MVA) method in Islamic commercial banks in Indonesia. The sample determination technique used in this study is to use the type of purposive sampling, namely the criteria of having financial reports published and audited in the period 2014 to 2016 and complete financial statements from the period 2014 to 2016 with calculations using the MVA method (Market Value Added. The results show that the financial performance of BUS in this period has a positive average value using EVA and MVA. This situation shows that the positive EVA and MVA values are in good condition and have more economic added value after the company pays all obligations to the funders or creditors according to their expectations, so that the company's profits provide economic value for the company.